Navigating through the nucleus with a virus - Castro, Ines J. de; Lusic, Marina (Current opinion in genetics & development, 2019)
In each cell, the hierarchical organisation of the ∼2m DNA fibre ensures different nuclear functions, particularly proper gene expression. Chromosomes are non-randomly positioned occupying specific chromosome territories in the 3D nuclear space and circumventing several nuclear landmarks the Nuclear Envelope with embedded Nuclear Pore Complexes, Splicing Speckles, PML bodies and many others. At a higher level of organisation, similarly regulated chromatin regions cluster together in so called Topologically Associated Domains, TADs, while on a smaller scale, DNA sequences wrapped around histones dictate binding of transcription factors or inhibitors that determine the level of chromatin compaction. As intracellular pathogens, viruses explore different cellular structures and functions to either promote their lytic infection or control the latent state of their replication cycles. Here we highlight the most recent discoveries on how different levels of nuclear architecture and genome are exploited by various human viruses.